MEMAKNAI PUTUS ASA DALAM PARADIGMA HENTI - HUSNIAH RAMADHANI PULUNGAN (IAIN Padangsidimpuan, 2017)
Despair caused by the loss of hope that makes a person stop hoping. Islam forbids it, because God has promised it easy for His servants who did not despair and continue to be patient in the face the tests of life. At the stop words are lexem HENTI which when analyzed morphologically based linguistics will be able to give a detailed understanding about the lexem. The analysis conducted by derivational and inflectional this will result ideosincretics of rules were found. Thus, an understanding of morphological standpoint this will provide benefits in the needs-oriented communication on the positive things. Finally, communication with the use of positive diction will encourage someone to have a mindset and a way of life that is better aligned with the values of Islam